Memoir of Siti Khadijah: my IIUM journey - Omar, Siti Khadijah (Universiti Teknologi MARA, Kedah, 2026)
The Academy of Language Studies at Universiti Teknologi MARA (UiTM) is thrilled to unveil the vibrant sixth edition of its e-magazine, The Epitome. This publication celebrates our passionate commitment and unwavering dedication to the art and craft of language and literature THE EPITOME emerges as a dynamic platform for a community of writers, educators, scholars, poets, and researchers all eager to share their unique perspectives, breakthroughs, wisdom, and tales This edition showcases a mix of creative writing genres, from the dramatic twists of playwriting to the introspective depths of personal essays including short stories songs speeches, memoirs, literary journalism, humorous writing lyric essays arid innovative essays with a rich tapestry of voices